An annotated checklist of cockroaches (Blattodea) from India - Gupta, Sunil Kumar; Chandra, Kailash (Zootaxa, 2019)
An updated checklist of Cockroaches (Blattodea) of 181 species belonging to 72 genera under 17 subfamilies and 6 families, including 89 endemic species from India have been provided. The study on the diversity of cockroaches globally shows that many species are yet to be discovered, since only 3.8% of the global species are known to India. The states with high number of records are Tamil Nadu (55 spp.), West Bengal (37 spp.), Arunachal Pradesh (25 spp.), Meghalaya & Sikkim (24 spp.) respectively. The dominant families are Blaberidae (83 spp.), Ectobiidae (53 spp.), Blattidae (24 spp.), Corydiidae (17 spp.), Nocticolidae (3 spp.) and Tryonicidae (1 spp.). The state-wise distribution records along with references, synonyms have also been incorporated.